RANCANGAN D-OPTIMAL MODEL MICHAELIS MENTEN DAN EMAX DENGAN MATLAB - Tatik Widiharih; Sri Haryatmi; Gunardi Gunardi; Yuciana Wilandari (MEDIA STATISTIKA, 2015)
Michaelis Menten and Emax models  are  widely used in chemistry, pharmacokinetics and pharmacodynamics areas. D-optimal criteria is criteria with the purpuse to minimize the variance of the estimator of parameters in the model. In this paper will discuss the D-optimal design for Michaelis Menten and Emax models with  homoscedastics  error assumtion.  Determination of D-optimal designs based on Generalied Equivalence Theorem Kiefer-Wolvowitz. We used minimally supported design with the proportion of  each design point is uniform, lower bound of design region is design point and the others are interior points.Keywords: D-optimal, Michaelis Menten, Emax, Minimally Supported Design, Homoscedastics